Correction: Validation of serological tests for the detection of antibodies against Treponema pallidum in nonhuman primates. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2015)
[This corrects the article DOI: 10.1371/journal.pntd.0003637.].